O quadro de escrever como mediador para construção de relações de autonomia no ambiente de sala de aula - MICCIONE, Jani Selma Morais (2006)
The blackboard nowadays has been, criticized by those teachers who consider it traditional. However some teachers and pedagogues, including myself, consider that since it is used in a different way, the blackboard has great importance for teaching and learning, mainly for mathematics. This essay is about a study done in a junior high school 7th grade group and its goal is to verify what are the reasons that make students participation on blackboard activities difficult. This study shows that the blackboard isnt, in its material form, a traditional recourse. In its use there are power relations that make the students do not accept to participate in its activities. The discussion happens around the necessity of involving the students and the teacher in interaction activities which channel is the blackboard since it is adequate for mathematics communication between teacher and students and among students.